2022
DOI: 10.1038/s41525-022-00341-w
|View full text |Cite
|
Sign up to set email alerts
|

Using coding and non-coding rare variants to target candidate genes in patients with severe tinnitus

Abstract: Tinnitus is the phantom percept of an internal non-verbal set of noises and tones. It is reported by 15% of the population and it is usually associated with hearing and/or brain disorders. The role of structural variants (SVs) in coding and non-coding regions has not been investigated in patients with severe tinnitus. In this study, we performed whole-genome sequencing in 97 unrelated Swedish individuals with chronic tinnitus (TIGER cohort). Rare single nucleotide variants (SNV), large structural variants (LSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…Seventeen genetic studies were included [ 8 , 9 , 35 49 ], with a global sample size of 294,143 subjects (45.4% males), and 55,267 patients with tinnitus (18.8% males).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen genetic studies were included [ 8 , 9 , 35 49 ], with a global sample size of 294,143 subjects (45.4% males), and 55,267 patients with tinnitus (18.8% males).…”
Section: Resultsmentioning
confidence: 99%
“…All the studies included reported no significant differences in terms of age between subgroups. Three studies excluded patients with SNHL [ 36 , 42 , 47 ], two studies reported no significant differences in audiograms between tinnitus and control subjects [ 39 , 40 ], six studies included subjects with some degree of hearing impairment, including SNHL [ 8 , 37 , 45 , 49 ], presbycusis [ 35 ], or noise-induced hearing loss [ 41 ], and the rest of them failed to report information on hearing stage [ 9 , 38 , 43 , 44 , 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pipeline has been used within the field of cancer research ( 22–27 ) and beyond, such as the identification of rare variants in tinnitus patients ( 28 ), finding SNPs in driver genes related to stress-response in cowpeas ( 29 ), the genomic profiling of wild and commercial bumble bee populations ( 30 ), or the Personal Genome Project-UK ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pipeline has been used within the field of cancer research [22][23][24][25][26][27] and beyond, such as the identification of rare variants in tinnitus patients [28], finding SNPs in driver genes related to stress-response in cowpeas [29], the genomic profiling of wild and commercial bumble bee populations [30], or the Personal Genome Project-UK [31].…”
Section: Introductionmentioning
confidence: 99%
“…The pipeline has been used within the field of cancer research [2227] and beyond, such as the identification of rare variants in tinnitus patients [28], finding SNPs in driver genes related to stress-response in cowpeas [29], the genomic profiling of wild and commercial bumble bee populations [30], or the Personal Genome Project-UK [31]. Here, we present a re-implementation of the nf-core/sarek pipeline using the Nextflow DSL2 framework, an extension of the Nextflow syntax allowing to develop pipelines in a modular fashion, which increases user-based customization to maintain a modern pipeline.…”
Section: Introductionmentioning
confidence: 99%